Dissociative Effect and Reorientation of Consciousness in the Movie Yuni and He Named Me Malala - Natasya Lawrencia; Danial Hidayatullah (Balai Bahasa Kalimantan Tengah, 2023)
This article aims to compare and investigate the movie Yuni (2021) and He Named Me Malala (2015) in terms of how the sociocultural environment affects the main characters' psychological conditions. Despite the differences in their sociocultural conditions, both characters experience some similarities with the recurring trauma, dissociative effect, and reorientation of consciousness. The phenomena is crucial to investigate because Franz Fanon has attempted to prove that psychoanalysis is not a universally applied theory. The purpose of this study is to find out the form of traumatic feelings experienced by the two main characters and identify how dissociative effects and reorientation of consciousness are presented due to traumatic events. The theory of literary trauma by Caruth is employed as the theory to be used in this research. The impact of Malala's and Yuni's traumatic experiences are significantly different. Yuni tends to have the effects of Post Traumatic Stress Disorder (PTSD), while Malala tends to have a Post Traumatic Growth (PTG). PTSD is regarded as a severe condition that needs expert care to manage and recover from. PTG, on the other hand, describes the positive psychological improvements that certain people may experience after a traumatic occurrence.AbstrakArtikel ini bertujuan membandingkan dan menyelidiki Yuni (2021) dan He Named Me Malala (2015) dalam kaitannya dengan bagaimana lingkungan sosiokultural memengaruhi kondisi psikologis tokoh utama. Terlepas dari perbedaan kondisi sosiokultural mereka, kedua karakter mengalami beberapa kesamaan dengan trauma berulang, efek disosiatif, dan reorientasi kesadaran. Fenomena ini penting untuk diselidiki karena Franz Fanon telah berusaha membuktikan bahwa psikoanalisis bukanlah teori yang diterapkan secara universal. Selain itu, tujuan dari penelitian ini adalah mengetahui bentuk perasaan traumatis yang dialami oleh kedua tokoh utama dan mengidentifikasi bagaimana efek disosiatif dan reorientasi kesadaran yang dihadirkan akibat peristiwa traumatis. Teori trauma sastra oleh Cathy Caruth digunakan sebagai teori yang akan digunakan dalam penelitian ini. Dampak pengalaman traumatis Malala dan Yuni sangat berbeda. Yuni cenderung mengalami Post Traumatic Stress Disorder (PTSD), sedangkan Malala cenderung mengalami Post Traumatic Growth (PTG). PTSD dianggap sebagai kondisi parah yang membutuhkan perawatan ahli untuk dikelola dan dipulihkan. PTG, di sisi lain, menggambarkan peningkatan psikologis positif yang mungkin dialami orang-orang tertentu setelah kejadian traumatis. Dari temuan ini, apa yang dikatakan Fanon bergantung pada situasi di sekitar subjek.